2013
DOI: 10.1111/boj.12054
|View full text |Cite
|
Sign up to set email alerts
|

The design of trapping devices in pollination traps of the genusArum(Araceae) is related to insect type

Abstract: Pollinators have long been known to select for floral traits, but the nature of this relationship has been little investigated in trap pollination systems. We investigated the trapping devices of 15 Arum spp. and compared them with the types of insects trapped. Most species shared a similar general design of trap chamber walls covered in downward-pointing papillate cells, lacunose cells in the chamber wall and elongated sterile flowers partially blocking the exit of the trap. However, there was significant var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Having landed on the appendage or spathe, insects then glide into the basal chamber, where some will deposit pollen on the receptive stigmas (Bröderbauer et al. , for details on the morphology of trapping mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…Having landed on the appendage or spathe, insects then glide into the basal chamber, where some will deposit pollen on the receptive stigmas (Bröderbauer et al. , for details on the morphology of trapping mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…These odor blends are thought to mimic the odor of dung or rotting organic matter, the natural brood sites of these Psychodidae (Lack and Diaz 1991). Pollinators are trapped in a highly specialized floral chamber (Bröderbauer et al 2013) until the day after VOC emissions (Gibernau et al 2004). As a result, we are able to accurately quantify the complete pollinator community attracted by each inflorescence, and unambiguously relate pollinator abundances to VOC emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Floral shape variation often reflects differences in plant pollination systems, particularly for plant species with specialized plant-pollinator interactions. Comparative studies have resulted in qualitative descriptions of these shape differences and multivariate analyses of floral trait measurements have, with varying degrees of success, shown that plant species can cluster in phenotype space according to general pollinator classes (Wilson et al 2004;Bröderbauer, Weber, and Diaz 2013). However, in comparison to these traditional approaches, GMM have the potential to provide additional and more accurate insights into the associations between floral shape variation and pollination biology (van der Niet et al 2010;Blanco-Pastor et al 2015).…”
Section: First Step Towards Investigating the Evolution Of Delphinieamentioning
confidence: 99%